Recent Change—River Run-off and Ice CoverRiver runoff - Apsite E; Bolek A; Filatov N; Kondratyev S; Korhonen J; Kriaučiūnienė J; Lindström G; Nazarova L; Pyrh A; Sztobryn M (Springer, 2022)
This chapter compiles and assesses information on run-off and discharge from rivers within the
Baltic Sea drainage basin. Some information is also available on ice duration on inland waterways. Although decadal and regional variability is large, no significant long-term change has been detected in total river run-off to the Baltic Sea over the past 500 years. A change in the timing of the spring flood has been observed due to changes in the timing of snowmelt. Change in temperature seems to explain change in run-off better than does precipitation. Later start dates for ice formation on waterways, and earlier ice break-up dates have resulted in shorter periods of ice cover.
Second Assessment of Climate Change for the Baltic Sea Basin